Wpływ nowelizacji dyrektywy 96/71/WE Parlamentu Europejskiego i Rady z dnia 16 grudnia 1996 r. dotyczącej delegowania pracowników w ramach świadczenia usług na statut stosunku pracy - Kurowski, Witold (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The Directive (EU) 2018/957 of the European Parliament and of the Council of 28 June 2018 introduced several changes to the Directive 96/71/EC on the posting of workers in the framework of the provision of services, affecting the posted worker’s employment relationships directly. Article 3(1) of the Directive 96/71/EC requires that an employer has to guarantee his workers posted to the Member State, the terms and conditions of employment, in matters listed in it, resulting from the law where the work is carried out, regardless of the law applicable to employment relationships. First of all, the Directive (EU) 2018/957 introduced the new concept of “remuneration” paid to the posted workers. Secondly, it extended the list of mattes in article 3(1) by adding point (h) — “the conditions of workers’ accommodation where provided by the employer to workers away from their regular place of work” and point (i) — “allowances or reimbursement of expenditure to cover travel, board and lodging expenses for workers away from home for professional reasons.” Finally, the Directive (EU) 2018/957 established the posting period, not clearly defined before, which should not last longer than 12 months (18 months when the service provider submits a motivated notification). This paper analyses the main changes introduced by the Directive (EU) 2018/957 amending the Directive 96/71/EC in the employment relationship field.